2015
DOI: 10.1096/fasebj.29.1_supplement.937.9
|View full text |Cite
|
Sign up to set email alerts
|

A Role for CHAC1 in Acetaminophen Hepatotoxicity

Abstract: Acetaminophen (APAP) is a commonly used pain reliever and a well‐established, dose‐related hepatotoxin. Hepatotoxicity occurs when metabolism of excessive APAP generates high concentrations of the reactive metabolite N‐acetyl‐p‐benzoquinone imine (NAPQI). NAPQI depletes cellular glutathione (GSH) and forms protein adducts leading to cellular stress, mitochondrial dysfunction, and, ultimately, oncotic necrosis of Zone 3 hepatocytes. The endoplasmic reticulum (ER) stress pathway is important to maintain cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is in favor of intracellular degradation of GSH in the liver of APAP-treated mice. Our result extends a single previous preliminary work reporting that overexpression of CHAC1 in HepG2 cells reduced GSH and increased APAP toxicity [28]. Further evaluation of the quantitative contribution of Chac1 to the APAP-induced GSH decrease is of interest because Chac1 could be a novel target to rescue hepatic GSH and reduce APAP toxicity.…”
Section: Discussionsupporting
confidence: 86%
“…This is in favor of intracellular degradation of GSH in the liver of APAP-treated mice. Our result extends a single previous preliminary work reporting that overexpression of CHAC1 in HepG2 cells reduced GSH and increased APAP toxicity [28]. Further evaluation of the quantitative contribution of Chac1 to the APAP-induced GSH decrease is of interest because Chac1 could be a novel target to rescue hepatic GSH and reduce APAP toxicity.…”
Section: Discussionsupporting
confidence: 86%
“…PLA2G4D also appears in the STRING network and interacts with CHAC1. Knock-out of CHAC1 in mice leads to decreased osteoblast differentiation and bone density (Crawford et al, 2016). PLA2G4D is part of the phospholipase A2 family, and it is present in the enriched gene set for the overrepresented pathway phospholipase-C pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Current results showed that regular exercise could signi cantly reduce "CHAC1" mRNA expression. It is an enzyme that could be upregulated in response to ER stress through "PERK/elF2α/ATF4/CHOP" signaling, Nrf2, ATF3 and P53 pathways [17]. CHAC1 is an enzyme that degrades GSH, which is an important antioxidant molecule.…”
Section: Chac1 Gclc Alox12mentioning
confidence: 99%
“…Crawford et al (2018) stated that genetic inhibition of CHAC1 in mice leads to numerous Modi cations in body con guration, including decreased amount of muscle tissue and changes in bone growth, which shows the importance of CHAC1 in muscles and bones proper regulation. In addition, CHAC1 could be a crucial factor in the development of muscle and bone pathology in conditions such as osteoporosis, aging, and muscle wasting [17]. Glutamate-cysteine ligase (GCL) as the rst rate-limiting enzyme of GSH biosynthesis is considered as well.…”
Section: Introductionmentioning
confidence: 99%